Comprehensive clinical hepatology - Bacon, Bruce R (Elsevier Mosby, 2006)
Authoritative and highly illustrated in full color, this comprehensive resource is the result of a joint effort of four experienced senior clinicians and educators. It focuses on the medical aspects of transplantation, offers an oasis of knowledge on key topics for clinical practice and examination, and discusses the newest developments in the field, including NASH and chronic viral hepatitis.Covers all aspects of medical transplantation.Features expert guidance and clinical coverage in one convenient volume.Uses full-color art work, clinical photographs, and time-saving tables for easy retrieval of information.Emphasizes key topics for clinical practice and certifying examinations.Incorporates the most recent advances in Hepatology, including NASH and chronic viral hepatitis.Features a BONUS CD-ROM containing all of the superb full-color illustrations from the book able to be downloaded into PowerPointT.
Keywords: nemoci jater; hepatitida; Liver Diseases; hepatologie; Hepatitis